Sistem Kendali Kenyamanan Lingkungan Rumah Menggunakan Metode Fuzzy Mamdani Dengan Teknologi IoT (Jurnal Ampere, 2025)
Environmental comfort within residential spaces plays a crucial role in enhancing the quality of life, prompting the development of automated control systems based on Internet of Things (IoT) technology. This study aims to design and implement an automated temperature control system to improve user comfort in homes. The system uses a BMP280 sensor to monitor temperature levels, applying the Mamdani Fuzzy Logic method to make control decisions for fan and Peltier thermoelectric devices. Lighting is controlled through a simple on/off system, while air quality is monitored with an MQ135 sensor without fuzzy logic processing. All sensor data is transmitted to an application built on MIT App Inventor via the MQTT protocol. Testing involves varying temperature levels to observe the system's response. The results show that the system effectively activates actuators based on the temperature and fuzzy rules designed. This approach provides an efficient and adaptive solution for achieving automatic environmental comfort in IoT-based residential environments